Implementación del modelo integrado de planeación y gestión en la alcaldía municipal de Iza - Boyaca (2021)
This article makes a diagnosis on the implementation of the integrated planning and management model from now on MIPG in the municipal mayor of Iza - Boyacá. Which is detailed, with a qualitative orientation, using as a tool the documentary observation collected in secondary sources and meeting with the municipal administration. According to the face-to-face visits and the interview with the planning secretary of the municipality of Iza - Boyacá, it was found that they carried out the implementation of MIPG in two phases: the first. Adequacy in the information found through an administrative act which created the institutional management and performance committee of the municipalityand the second the implementation of the seven dimensions with the 18 policies. The entities must apply the model to generate confidence among citizens in the execution of financial resources and the expected results.